Influence of anxiety state on the performance stability of top-level rhythmic gymnasts - Fan, L.; Cao, C.; Tang, H. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The exercise of athletic skills is subject to the influence of anxiety either in temperament or in performance. Since psychological reaction can be seen from physiological changes, subjective responses, psychological operation and objective reality, psychological anxiety and athletic performance are closely related - anxiety on the part of contestants can result in either loss of control or more confidence of success in competition. The present paper attempts to describe the overall playing condition of the Chinese team of rhythmic gymnasts, and analyze accordingly the influence and effect of performance anxiety on performance stability. Methods The Spielberg Questionnaire of Temperamental Anxiety and the Martens Table of Performance Anxiety are used in this research together with the on-the-spot statistics of 84 excellent Chinese athletes, 18 testing competitions by the Olympic Rhythmic Gymnastics individual players and the Chinese National Games, three interviews with rhythmic gymnastics coaches, judges, training experts and sports psychologists, and many talks with rhythmic gymnasts on their experiences and feelings. Results 1. In the questionnaires, the coaches' evaluations like "poor ability in self-regulation" and "poor ability in psychological endurance" are closely related with the athletes' anxiety in competition. 2. Rhythmic gymnasts' state of performance anxiety has different degrees of impact on their stability in competition. 3. As for the Chinese rhythmic gymnasts, the level of temperamental anxiety shows a normal distribution ranging between 39.6±6.3. 4. Rhythmic gymnasts' level of performance anxiety has a certain influence on their chance of success in competition. Low cognitive anxiety and high playing confidence can help increase the stability in performance. 5. Athletes show significantly different levels of physical anxiety in different levels of competition. Higher level of competition leads to higher level of physical anxiety. 6. Rhythmic gymnasts' playing confidence has greater influence on performance in competition than cognitive anxiety and physical anxiety do. 7. At certain stages of training, coaches should bring the quantity of training under reasonable control in accordance with the relevant statistics. Ratios of first success and successful training are the best index for score forecasting. Therefore, coaches should make reasonable use of the ratio of first success.